Faktor yang Berhubungan dengan Kualitas Hidup Penyintas Covid-19 di RSUD M Yunus dan RSUD Mukomuko - Catur Ramadanti; Dhiny Easter; Nurul Aryastuti (Malahayati Nursing Journal, 2024)
ABSTRACT Quality of life as an individual's perception of his life in society in the context of culture and existing value systems related to goals, expectations, standards and also concerns To assess the quality of life of COVID-19 survivors, measurements can be carried out with the ST George Respiratory Questionnare (SGRQ). Factors related to the quality of life of Covid-19 survivors at M Yunus Regional Hospital, Bengkulu and Mukomuko Regional Hospital in 2022. The analysis used to test the 2 associations of 2 categorical variables used a statistical test, namely the Chi Square test. The multivariate test used is logistic regression which is a mathematical model approach used to analyze the relationship of one or more independent variables with dependent categories that are dichotomous/binary with P Value 0.05. The results of this study where the variables used were physical health, gender, age and level of education with the results of each p value physical health = 0.001, sex = 0.007, age = 0.007 and Comorbidities history = 0.000. Which means it has a relationship with the dependent variable, namely quality of life. The dominant factor in the multivariate test is physical health with an effect of 8.264 times on quality of life in survivors of Covid-19.  Suggestions for hospitals need to intensify health promotion and education related to symptoms that may arise after being exposed to Covid-19 infection and the importance of efforts to control Covid-19 virus infection so that they are not infected again in the future, especially in high-risk patients, such as elderly patients, immunocompromised as well as with other co-morbidities. Keywords: Quality Of Life, Covid-19 Survivors  ABSTRAK Kualitas hidup sebagai persepsi individu terhadap kehidupannya di masyarakat dalam konteks budaya dan sistem nilai yang ada yang terkait dengan tujuan, harapan, standar dan juga perhatian Untuk menilai kualitas hidup para penyintas COVID-19 dapat dilakukan pengukuran dengan ST George Respiratory Questionnare (SGRQ). Faktor yang berhubungan dengan kualitas hidup penyintas Covid-19 Di RSUD M Yunus Bengkulu dan RSUD Mukomuko Tahun 2022. Analisa yang digunakan untuk menguji 2 asosiasi 2 variabel kategorik digunakan uji statistik yaitu uji Chi Square. Uji multivariat yang digunakan adalah regresi logistic yang merupakan salah satu pendekatan model matematis yang digunakan untuk menganalisis hubungan satu atau beberapa variabel independen dengan dependen kategori yang bersifat dikotom/binary dengan P Value 0,05. Hasil dari penelitian ini dimana variabel yang digunakan adalah Kesehatan fisik, jenis kelamin, usia dan riwayat komorbid dengan hasil masing-masing p value Kesehatan fisik=0,001, jenis kelamin=0,007, usia=0,007 dan riwayat komorbid=0,000. Yang artinya memiliki hubungan dengan variabel dependennya yaitu kualitas hidup. Faktor dominan pada uji multivariat adalah Kesehatan fisik dengan pengaruh sebesar 8,264 kali terhadap kualitas hidup pada penyintas Covid-19. Saran bagi rumah sakit perlu menggencarkan promosi kesehatan serta edukasi terkait gejala yang mungkin timbul pasca terkena infeksi Covid-19 serta pentingnya upaya pengendalian infeksi virus Covid-19 agar tidak terjangkit kembali kemudian hari terutama pada pasien-pasien   dengan resiko tinggi, seperti pasien usia lanjut, immunocompromised serta dengan komorbid lainnya. Kata Kunci: Kualitas Hidup, Penyintas Covid– 19